Pengembangan Smart Learning Berbasis Sistem Pakar Pada Mata Kuliah Kriptografi - Mochammad Iswan; M Syaifuddin (Syntax : Journal of Software Engineering, Computer Science and Information Technology, 2022)
Abstract: The development of science and technology requires universities not only material but also have the ability in their respective fields including cryptography. To overcome the shortcomings in these learning activities, a project-based blended learning model was developed. The development carried out in this study uses the Puslitjaknov development model which reduces the Borg and Gall stages into five stages, namely product analysis, initial product design, expert validation and revision, field trials and implementation. The subjects of this study were STMIK Triguna Dharma students who took Cryptography courses in the 2020 academic year. Data was collected by means of interviews, observations, questionnaires and tests. Data analysis used quantitative and qualitative methods to produce products in the form of books, modules, lesson plans and manuals for using learning applications. Product validation by experts, practicality tests carried out by users and effectiveness tests with student learning outcomes. Based on the results of data analysis, the results of this study are: 1) Research has succeeded in developing a project-based blended learning model in cryptography courses. 2) The developed syntax learning model consists of 9 stages/syntax. 3) In supporting learning activities, DIKTAT, RPS and student guides. All products and models that have been developed and categorized are valid, practical and effective. Keywords: Blended Learning, Project Base Learning, Cryptografy Abstrak: Perkembangan ilmu pengetahuan dan teknologi menuntut perguruan tinggi tidak hanya sekedar materi tetapi juga memiliki kemampuan di bidangnya masing-masing termasuk kriptografi. Untuk mengatasi kekurangan dalam kegiatan pembelajaran tersebut, maka dilakukan pengembangan model blended learning berbasis proyek. Pengembangan yang dilakukan dalam penelitian ini menggunakan model pengembangan Puslitjaknov yang mereduksi tahapan Borg and Gall menjadi lima tahapan yaitu analisis produk, desain produk awal, validasi dan revisi ahli, uji coba lapangan dan implementasi. Subyek penelitian ini adalah mahasiswa STMIK Triguna Dharma yang mengambil mata kuliah Kriptografi pada tahun ajaran 2020. Pengumpulan data dilakukan dengan wawancara, observasi, angket dan tes. Data dianalisis menggunakan metode kuantitatif dan kualitatif untuk menghasilkan produk penelitian berupa buku, modul, rencana pembelajaran dan manual penggunaan aplikasi pembelajaran. Validasi produk oleh ahli, uji kepraktisan yang dilakukan oleh pengguna dan uji keefektifan dengan hasil belajar siswa. Berdasarkan hasil analisis data, maka hasil penelitian ini adalah: 1) Penelitian telah berhasil mengembangkan model blended learning berbasis proyek pada mata kuliah kriptografi. 2) Sintaks model pembelajaran yang dikembangkan terdiri dari 9 tahapan/sintaks. 3) Dalam menunjang kegiatan pembelajaran, DIKTAT, RPS dan panduan mahasiswa. Semua produk dan model yang dikembangkan telah dikembangkan dan dikategorikan valid, praktis dan efektif. Kata Kunci: Blended Learning, Project Base Learning, Kriptografi